STUDI TENTANG RESIKOBANJIR DI KABUPATEN LAMONGAN PROVINSI JAWA TIMUR - Ilham B Mataburu (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2013)
ABSTRACT This study aims to determine the extent of the flood hazard, vulnerability and risk levels of flooding in Lamongan, East Java Province. This research uses descriptive method with scoring of unit region and areal differentiations. Results of this study indicate that the basin-shaped area of Lamongan causing this area to be an area with a high risk of flooding. There are 61 villages out of 474 villages were inundated with threat levels low, medium and high. there are 22 villages with low hazard level, 17 villages with medium hazard levels and 22 villages with a high hazard level. Based on the analysis of the elements of vulnerability, to areas with low vulnerability category contained in 7 sub-districts, medium vulnerability found in 15 sub-districts and region with high vulnerability was found in 5 sub-districts. Result of flood risk analysis, it is known that high-risk villages are generally found in the near of Bengawan Solo river and Bengawan Jero river. The whole village is in this category amounted to 13 villages located in three districts namely (1) Kecamatan Babat there are 4 villages, (2) Kecamatan Karangbinangun there 1 village, (3) and in Kecamatan Laren there are 4 villages. Medium risk region there are at 38 villages in 11 sub-districts. The villages are generally located near along stream of the Bengawan Solo river and Bengawan Jero river. Kecamatan Karangbinangun and Laren is the highest number of villages with medium risk of flooding. They have each 12 and 10 villages with a medium risk of flooding. For region with low flood risk is located in 10 villages in 5 sub-districts. Keyword: Hazard, vulnerability, flood risk.